Pengembangan Bahan Ajar Etnomatematika Bernuansa Rumah Adat Provinsi Banten Pada Sekolah Dasar - Eka Berliana Nur Oktaviana; Desi Setiyadi; Fitriana Siregar (Elementary Teacher Education Program, Majalengka University, 2023)
In the era of globalization, education is required to keep up with the times. Where many outside cultures have entered Indonesia and our culture will become extinct. The purpose of making this teaching material is to expand and develop teaching materials with ethnomathematics nuances of Banten's typical traditional houses on building space material in elementary schools. The method used in this research is Research and Development (R&D) which has the steps of Define, Design and Develop. Elementary school located in Tangerang is the subject of this research and with a combination of data collection techniques as follows: using scores from verifiers, teachers, and peers. The development of this educational material follows the 4-D model, namely identifying, designing and developing. At each step, the definition requires a context about the importance of ethnomathematics mathematics teaching materials nuanced with typical Banten traditional houses that need to be applied in contextual learning. The design stage carries out educational document design activities starting from the cover page, content and conclusion. The development stage is to revise the raw draft to achieve the best validity score of 4.55 in the validity category and can be used academically